Arbitration as an Alternative Mechanism of a Tax Dispute Resolution - Tsiklauri, Ilia (Alternative Dispute Resolution Yearbook, 2019)
Arbitration is an alternative method of protection of right. Since the second half of the 20th century it becomes more and more popular. According to the international practice, arbitration considers disputes of many types, including tax dispute. Dispute may be considered on the national level, between the tax authority and tax payer, as well as on the international level as a dispute between two states. The goal of the article is to consider the essence of the institute of arbitration, expedience of its application to tax disputes, advantages and disadvantages, as well as the prospects of introduction of this institute in Georgia.